Does gene flow aggravate or alleviate maladaptation to environmental stress in small populations?. (4th February 2019) - Fitzpatrick, Sarah W.; Reid, Brendan N.
Abstract: Environmental change can expose populations to unfamiliar stressors, and maladaptive responses to those stressors may result in population declines or extirpation. Although gene flow is classically viewed as a cause of maladaptation, small and isolated populations experiencing high levels of drift and little gene flow may be constrained in their evolutionary response to environmental change. We provide a case study using the model Trinidadian guppy system that illustrates the importance of considering gene flow and genetic drift when predicting (mal)adaptive response to acute stress. We compared population genomic patterns and acute stress responses of inbred guppy populations from headwater streams either with or without a recent history of gene flow from a more diverse mainstem population. Compared to "no‐gene flow" analogues, we found that populations with recent gene flow showed higher genomic variation and increased stress tolerance—but only when exposed to a stress familiar to the mainstem population (heat shock). All headwater populations showed similar responses to a familiar stress in headwater environments (starvation) regardless of gene flow history, whereas exposure to an entirely unfamiliar stress (copper sulfate) showed population‐level variation unrelated to environment or recent evolutionary history. Our results suggest that (mal)adaptive responses to acutely stressful environments are determined in part by recent evolutionary history and in part by previous exposure. In some cases, gene flow may provide the variation needed to persist, and eventually adapt, in the face of novel stress.